Biochemical and histological alterations of Mytilus galloprovincialis digestive gland - R Auriemma (Invertebrate Survival Journal, 2004)
Electrophoretical and histological analysis were performed on Mytilus galloprovincialis digestivegland samples, in order to detect the presence of a previously identified protein ca 30 kDa MW,synthesized during Dinophysis spp. blooms, and assess a possible correlation between the occurrenceof this protein and okadaic acid (OA) exposure by ingestion. Mussels were sampled monthly from July2000 to November 2001 in the Gulf of Trieste (upper Adriatic Sea) and immediately processed. Parallelsamples were maintained in sea water plastic tanks and fed with marine invertebrate feed mixed withOA and derivatives at different concentration of toxins for each experimental group (25 mg, 50 mg, 100mg). In tank reared mussels fed with OA, degeneration of digestive cells and appearance of 24.6 kDaprotein were observed, while in wild mussels, neither histological alterations nor presence of a 24.6kDa protein, were detected. A correlation between the toxins concentration and time of appearancewas highlighted, to demonstrate this protein is synthesized in response to OA and derivativesexposure. About the identity of 24.6 kDa protein, it could be an enzyme involved in detoxificationreactions, probably Glyoxalase I.